Jamak dan Qasar Salat dalam Islam: Telaah terhadap Pemikiran M. Hasbi Ash-Shiddieqy - Muhammad Iqbal (TAFSE: Journal of Qur'anic Studies, 2017)
Hasbi Ash-Shiddieqy is a scholar who asserts that a Muslim can perform multiple prayers without excuse. This thought is different from the majority of other scholars who stipulate certain conditions for the permissibility of performing plural prayers. From the problems above, it is necessary to study the main ideas that underlie Hasbi's understanding of the issue. This study is bibliographic in nature by using Hasbi's books as basic reference materials. The results of the study showed that Hasbi allowed plural prayers to be performed even without the age of consent. The permissibility of having multiple prayers in a state of residence and rain is used as an excuse for the ability to perform multiple prayers without excuse. This is based on a hadith which explains that the Prophet had performed plural and qasar prayers only to make it easier for his people. Hasbi's thinking only prioritizes understanding textually without looking at the asbab al-wurud hadith. Meanwhile, al-Nawawi and Yusuf al-Qaradawi did not allow plural without any excuse on the grounds that plural and qasar prayers are rukhsah from Allah. Meanwhile, according to Hasbi, the permissibility of plural and qasar without aging is based on the that Allah does not want trouble for His servants. According to him, everything that can be simplified must be made easier, including in matters of worship. Hasbi Ash-Shiddieqy seorang ulama yang menegaskan bahwa seorang muslim dapat menjamak salat tanpa uzur. Pemikiran ini berbeda dengan mayoritas ulama lainnya yang menetapkan syarat-syarat tertentu terhadap kebolehan melakukan salat jamak. Dari persoalan di atas maka perlu kajian mengenai pokok-pokok pikiran yang mendasari pemahaman Hasbi dalam persoalan tersebut. Kajian ini bersifat kepustakaan dengan menjadikan buku-buku Hasbi sebagai bahan rujukan dasar. Hasil penelitian menunjukkan bahwa Hasbi membolehkan salat jamak dilakukan meskipun tanpa uzur. Kebolehan jamak salat dalam keadaaan bermukim dan hujan dijadikannya  sebagai alasan untuk kebolehan menjamak salat tanpa uzur. Hal ini berlandaskan pada hadis yang menerangkan bahwa Nabi pernah melakukan jamak dan qasar salat hanya semata-mata untuk memudahkan umatnya. Pemikiran Hasbi hanya mengedepankan pemahaman secara tekstual tanpa melihat asbab al-wurud hadis. Sementara al-Nawawi dan Yusuf al-Qaradhawi tidak membolehkan jamak tanpa ada uzur dengan alasan bahwa jamak dan qasar salat merupakan rukhsah dari Allah. Sedangkan menurut Hasbi, kebolehan jamak dan qasar tanpa uzur didasarkan bahwa Allah tidak menginginkan kesusahan bagi hamba-Nya. Menurutnya segala sesuatu yang bisa dipermudah harus dipermudah termasuk dalam persoalan ibadah.